1971
DOI: 10.1901/jeab.1971.15-83
|View full text |Cite
|
Sign up to set email alerts
|

COLLATERAL BEHAVIOR OF THE PIGEON DURING CONDITIONED SUPPRESSION OF KEY PECKING1

Abstract: Ethological recording procedures measured collateral behavior in pigeons whose key-pecking performance was suppressed during a tone that ended with unavoidable electric shock. Independent recordings of gross behavior were made by two observers throughout 60-sec intervals immediately before, during, and after tone presentation. Results indicated significant reductions in the frequency of collateral movements and an increase in the time between successive movements during tone presentations. These effects were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
2
17
1
Order By: Relevance
“…Bolles based his theory on a review of the literature involving rats. The evidence presented in this paper as well as by Smith and Keller (1970), Gustavson, et al, (1971), Stein, Hoffman, and Stitt (1971) and otlhers suggest the point is equally well taken withi pigeons.…”
Section: Resultssupporting
confidence: 69%
“…Bolles based his theory on a review of the literature involving rats. The evidence presented in this paper as well as by Smith and Keller (1970), Gustavson, et al, (1971), Stein, Hoffman, and Stitt (1971) and otlhers suggest the point is equally well taken withi pigeons.…”
Section: Resultssupporting
confidence: 69%
“…The data indicate that one cannot always equate suppression with freezing, or that there is no specific motorrespondent classically conditioned to the CS. The present data, then, do not agree with the conclusion drawn by Stein et al (1971) from their pigeon's pecking suppression experiment that the freezing is the interfering incompatible respondent. It should be noted, however, that they used only a single level of shock intensity.…”
Section: Discussioncontrasting
confidence: 99%
“…First, Dinsmoor (1954Dinsmoor ( , 1955 and Weiskrantz (1968) pointed out the possibility that the CS would lead to an increase in the frequency of other behavior (operants and respondents) incompatible with the baseline response. Brday and Hunt (1955) and Stein, Hoffman, and Stitt (1971), on the other hand, suggested that " freezing " was the respondent incompatible with the baseline response. Perhaps the best and only experiment, in which systematic measurements of actual incompatible response or responses covarying with suppression were made, is the pecking suppression experiment with pigeon performed by Stein et al (1971).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found only two experiments addressed to this question. Hoffman and Barrett (1971) and Stein, Hoffman, and Stitt (1971) found reductions in food-reinforced responding and other overt activities of pigeons during the CS. A parallel experiment with an avoidance baseline has not been done and was the primary purpose of this experiment.…”
mentioning
confidence: 94%